Cdc42-dependent actin dynamics controls maturation and secretory activity of dendritic cells - Schulz, Anna M.; Stutte, Susanne; Hogl, Sebastian; Luckashenak, Nancy; Dudziak, Diana; Leroy, Celine; Forne, Ignasi; Imhof, Axel; Mueller, Stephan A.; Brakebusch, Cord H.; Lichtenthaler, Stefan F.; Brocker, Thomas (The Journal of Cell Biology, 2015)
Cell division cycle 42 (Cdc42) is a member of the Rho guanosine triphosphatase family and has pivotal functions in actin organization, cell migration, and proliferation. To further study the molecular mechanisms of dendritic cell (DC) regulation by Cdc42, we used Cdc42-deficient DCs. Cdc42 deficiency renders DCs phenotypically mature as they up-regulate the co-stimulatory molecule CD86 from intracellular storages to the cell surface. Cdc42 knockout DCs also accumulate high amounts of invariant chain-major histocompatibility complex (MHC) class II complexes at the cell surface, which cannot efficiently present peptide antigens (Ag's) for priming of Ag-specific CD4 T cells. Proteome analyses showed a significant reduction in lysosomal MHC class II-processing proteins, such as cathepsins, which are lost from DCs by enhanced secretion. As these effects on DCs can be mimicked by chemical actin disruption, our results propose that Cdc42 control of actin dynamics keeps DCs in an immature state, and cessation of Cdc42 activity during DC maturation facilitates secretion as well as rapid up-regulation of intracellular molecules to the cell surface.
EVALuna2:19559